Tinjauan Kriminologi Tindak Kekerasan Bullying di Kalangan Pelajar - Ni Kadek Nisa Alfiyana; Anak Agung Sagung Laksmi Dewi; I Made Minggu WIdyantara (Jurnal Interpretasi Hukum, 2022)
Bullying is an action taken by someone to attack someone not only physically but also psychologically. The development of the times makes it easier for someone to interact, so that someone, especially among students, is easy to do bullying which is mostly caused by promiscuity, lack of attention from parents and a free environment. This study aims to analyze and describe the criminology of violent acts of bullying among students. The research method used is Empirical Law research using the applicable legislation approach and goes directly to the field to conduct research. The results of this study indicate that bullying is caused by internal factors originating from oneself and external factors originating from promiscuity in the surrounding environment. Criminal sanctions against perpetrators of bullying are ensnared by law Article 80 paragraph (1) Jo which is regulated in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection.